The onset or exacerbation of lichen planus following COVID-19 and vaccination against COVID-19 - Funda Tamer (Termedia Publishing House, 2023)
Lichen planus is a chronic inflammatory cutaneous disease which is characterized by itchy papules as well as involvement of hair, nails and mucosa. Lichen planus shows clinical diversity since various subtypes and uncommon clinical presentations of the disease have been reported. The etiopathogenesis of lichen planus has not been completely elucidated yet. However, lichen planus has been related to viral infections such as hepatitis C virus, human papillomavirus and herpes simplex virus infections and vaccination such as influenza and hepatitis B virus vaccines. Lichen planus has also been reported following Coronavirus disease 2019 (COVID-19) and vaccination against COVID-19. Proinflammatory cytokine synthesis due to T cell activation has been implicated in the development of lichen planus after COVID-19 and COVID-19 vaccination. Herein, studies that reported the onset or exacerbation of lichen planus following COVID-19 and vaccination against COVID-19 have been reviewed in PubMed database.